Production of Functional Gametes from Cryopreserved Primordial Germ Cells of the Japanese Quail - NAKAMURA, Yoshiaki (The Society for Reproduction and Development, 2013)
The Japanese quail (Coturnix japonica) is a valuable bird as both an experimental animal, for a wide range of scientific disciplines, and an agricultural animal, for the production of eggs and meat. Cryopreservation of PGCs would be a feasible strategy for the conservation of both male and female fertility cells in Japanese quail. However, the effects of freeze-thaw treatment on viability, migration ability and germline transmission ability of quail PGCs still remain unclear. In the present study, male and female PGCs were isolated from the blood of 2-day-old embryos, which were cooled by slow freezing and then cryopreserved at –196 C for 77–185 days, respectively. The average recovery rate of PGCs after freeze-thawing was 47.0%. The viability of PGCs in the frozen group was significantly lower than that of the control group (P<0.05) (85.5% vs. 95.1%). Both fresh and Frozen-thawed PGCs that were intravascularly transplanted into recipient embryos migrated toward and were incorporated into recipient gonads, although the number of PGCs settled in the gonads was 48.5% lower in the frozen group than in the unfrozen control group (P<0.05). Genetic cross analysis revealed that one female and two male recipients produced live progeny derived from the frozen-thawed PGCs. The frequency of donor-derived offspring was slightly lower than that of unfrozen controls, but the difference was not significant (4.0 vs. 14.0%). These results revealed that freeze-thaw treatment causes a decrease in viability, migration ability and germline transmission ability of PGCs in quail.